Initial Development and Psychometric Properties of a New Measure of Substance Use Disorder "Recovery Progression": The Recovery Progression Measure (RPM). (28th July 2016) - Elison, Sarah; Davies, Glyn; Ward, Jonathan
ABSTRACT: There is a growing literature around substance use disorder treatment outcomes measures. Various constructs have been suggested as being appropriate for measuring recovery outcomes, including "recovery capital" and "treatment progression." However, these previously proposed constructs do not measure changes in psychosocial functioning during the recovery process. Therefore, a new psychometric assessment, the "Recovery Progression Measure" (RPM), has been developed to measure this recovery oriented psychosocial change. Aims : The aims of this study were to evaluate the reliability and factor structure of the RPM via data collected from 2218 service users being treated for their substance dependence. Method : Data were collected from service users accessing the Breaking Free Online (BFO) substance use disorder treatment and recovery program, which has within its baseline assessment a 36-item psychometric measure previously developed by the authors to assess the six areas of functioning described in the RPM. Reliability analyses and exploratory factor analyses (EFA) were conducted to examine the underlying factor structure of the RPM measure. Results : Internal reliability of the RPM measure was found to be excellent (α > .70) with the overall assessment to have reliability α = .89, with item-total correlations revealing moderate–excellent reliability of individual items. EFA revealed the RPM to contain an underlying factor structure of eight components. Discussion : This study provides initial data to support the reliability of the RPM as a recovery measure. Further work is now underway to extend these findings, including convergent and predictive validity analyses.